2010
DOI: 10.3727/096368910x504496
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Amnion Epithelial Cells Reduces Hepatic Fibrosis in Immunocompetent CCl4-Treated Mice

Abstract: Chronic liver injury and inflammation lead to hepatic fibrosis, cirrhosis, and liver failure. Embryonic and mesenchymal stem cells have been shown to reduce experimental liver fibrosis but have potential limitations, including the formation of dysplastic precursors, tumors, and profibrogenic cells. Other stem-like cells may reduce hepatic inflammation and fibrosis without tumor and profibrogenic cell formation. To test this hypothesis we transplanted human amnion epithelial cells (hAEC), isolated from term del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 42 publications
(67 reference statements)
10
142
1
1
Order By: Relevance
“…53 In detail, AM-hMSCs may mediate the tumortargeting effects of immunocytes by regulating the expressions of various cytokines such as tumor necrosis factor-a and ILs. 55 For instance, ILs may help immune systems by activating natural killer cells that can directly target human cancers. The results from these studies demonstrated that hAMS and hAFS have potential antitumor effects.…”
Section: Non-engineered Stem Cells Transplantation Strategiesmentioning
confidence: 99%
“…53 In detail, AM-hMSCs may mediate the tumortargeting effects of immunocytes by regulating the expressions of various cytokines such as tumor necrosis factor-a and ILs. 55 For instance, ILs may help immune systems by activating natural killer cells that can directly target human cancers. The results from these studies demonstrated that hAMS and hAFS have potential antitumor effects.…”
Section: Non-engineered Stem Cells Transplantation Strategiesmentioning
confidence: 99%
“…Based on these findings it was postulated that its therapeutic effect might be due to paracrine activation rather than to the hAECs per se. Other workers have shown that hAECs injection improves liver function, reduces hepatocyte apoptosis, and decreases hepatic inflammation and fibrosis in a CCL4-induced liver fibrosis model in wild-type mice [87]. In this study no obvious rejection response was seen 2 weeks after hAECs transplantation.…”
Section: Liver Fibrosismentioning
confidence: 50%
“…Important for the treatment of liver diseases by CTx, AE cells demonstrate hepatic gene expression and functions at a level of mature hepatocytes following implantation into the livers of SCID mice, which suggest they differentiate into hepatocyte-like cells once engrafted in the liver parenchyma (Miki & Strom, 2006;Marongiu et al, 2011). Undifferentiated AE cells were able to functionally engraft into the livers of immunocompromised mouse models of liver damage resulting in a reduction of hepatic fibrosis, inflammation, and hepatocyte apoptosis (Manuelpillai et al, 2010;Marongiu et al, 2011). In addition, AE cells have also been used in clinics to correct lysosomal storage diseases with no adverse effects (Yeager et al, 1985;Scaggiante et al, 1987;Sakurgawa et al, 1992).…”
Section: Ae Cell Transplantationmentioning
confidence: 95%